2020
DOI: 10.1038/s41598-020-68618-7
|View full text |Cite
|
Sign up to set email alerts
|

Are endemic species necessarily ecological specialists? Functional variability and niche differentiation of two threatened Dianthus species in the montane steppes of northeastern Iran

Abstract: Endemic species are believed to converge on narrow ranges of traits, with rarity reflecting adaptation to specific environmental regimes. We hypothesized that endemism is characterized by limited trait variability and environmental tolerances in two Dianthus species ( Dianthus pseudocrinitus and Dianthus polylepis ) endemic to the montane steppes of northeastern Iran. We measured leaf functional traits and calculated Grime’s competitor/stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…We collected the leaves from robust and well‐grown plants. Leaf material was collected from 10 individuals of each species (Behroozian et al, 2020 ), packed in moist paper bags, sealed in plastic bags and stored in a thermal box until storage at 4℃ for 12–24 hr. Depending on the size of leaves, 2–10 undamaged, fully expanded young leaves (including the petiole) were measured per individual.…”
Section: Methodsmentioning
confidence: 99%
“…We collected the leaves from robust and well‐grown plants. Leaf material was collected from 10 individuals of each species (Behroozian et al, 2020 ), packed in moist paper bags, sealed in plastic bags and stored in a thermal box until storage at 4℃ for 12–24 hr. Depending on the size of leaves, 2–10 undamaged, fully expanded young leaves (including the petiole) were measured per individual.…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, the alteration of phenotype by polyploidy suggests that plant functioning and tness may be fundamentally changed, but a preliminary classi cation of the species in our dataset according to Grime's CSR ecological strategies (method of Pierce et al 2017) showed that no particular strategy class was associated with polyploidy: species adapted to survive competition, stress or disturbance all exhibited an extremely wide range of chromosome numbers (data not shown). Rather than re ecting tness and adaptation, the high incidence of endemic polyploids could depend mainly on limited time for dispersal and colonizing new areas, as has been suggested for certain species (Behroozian et al 2020). Indeed, it has been determined that polyploid plant species rely mainly on vegetative reproduction (Herben et al 2017), which is usually ineffective for wide or rapid dispersal (Winkler and Fischer 2001;Herben et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For many endemics, reasons for range restriction are evident. For example, they may be limited to a small area because they can occupy a limited ecological niche (Williams et al 2009), or have originated by hybridization and occur only in the area of contact between the progenitor species (Grünig et al 2021), they may be relict species remaining from a much wider past range (paleo-endemics; Petrova et al 2015) or are recent species (neo-endemics, sensu Stebbins and Major 1965) yet to disperse beyond the centre of origin (Behroozian et al 2020). An additional explanation may lie with genome duplication (polyploidy), which effectively represents an 'instantaneous', sympatric speciation mechanism (Mayr 1963), and can be a major driver of plant evolution (Levin 1983;Otto and Whitton 2000;Soltis et al 2014;Van de Peer 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal that typically only found in defined geographic area, or called endemic species, are characteristic elements of local biodiversity (Behroozian et al, 2020). So that, endemic species become interesting object material for research because of its unique characteristic.…”
Section: Introductionmentioning
confidence: 99%